2013
DOI: 10.3109/00365521.2013.832370
|View full text |Cite
|
Sign up to set email alerts
|

Card15mutations and gastric cancer in a Portuguese population

Abstract: BACKGROUND. CARD15 is involved in the innate immune response and mutations of this gene have been linked with increased risk of Crohn's disease and colorectal cancer. The relation between CARD15 mutations and gastric cancer (GC) remains controversial. AIMS. To assess whether CARD15 mutations are risk factors for GC in Portugal and whether there are genotype-phenotype correlations in these patients. METHODS. The 3 main CARD15 mutations (3020insC, R702W and G908R) were searched in 150 patients with GC and in 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 78 publications
0
5
0
2
Order By: Relevance
“…It is suggested that susceptibility to breast cancer and age at diagnosis of breast cancer are different multifactorial traits. There were other reports that indicated that specific polymorphisms may be associated with risk of a disease or the age at which the disease is diagnosed ( 12 , 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is suggested that susceptibility to breast cancer and age at diagnosis of breast cancer are different multifactorial traits. There were other reports that indicated that specific polymorphisms may be associated with risk of a disease or the age at which the disease is diagnosed ( 12 , 13 ).…”
Section: Resultsmentioning
confidence: 99%
“…16 Our group already proved that L1007fsinsC variant is a risk factor for intestinal-type GC in Portugal. 12 However, in this work, it was not possible to evaluate the potential correlation of H. pylori infection with NOD2 genetic patterns.…”
Section: Introductionmentioning
confidence: 96%
“…The NOD2 gene, also called CARD15 (caspase recruitment domain family 15) can have an important role in H. pylori infection and GC. 6,10,12,13 Presence of polymorphisms in this gene have been associated with increased risk for gastrointestinal cancer although a recent general population study involving a large number of individuals did not confirm this correlation. 10,14 Another study even detected a negative association between some NOD2 polymorphisms and the risk of GC.…”
Section: Introductionmentioning
confidence: 96%
“…El estudio en pacientes con SL, PAF y CCR esporádico no reveló diferencias estadísticamente significativas con el grupo control en ninguna de las variantes estudiadas. Estos polimorfismos también se han evaluado en pacientes diagnosticados con cáncer gástrico sin observar asociaciones entre las variantes y la aparición de la enfermedad (157). Sin embargo, estas variantes se han asociado con la enfermedad de Crohn ( 157), colitis ulcerosa (159) y el cáncer colorrectal, aunque en este último caso hay informaciones contradictorias respecto al alelo que aumenta la susceptibilidad (160).…”
Section: Análisis De Polimorfismos En Genes Relacionados Con La Autofunclassified
“…Estos polimorfismos también se han evaluado en pacientes diagnosticados con cáncer gástrico sin observar asociaciones entre las variantes y la aparición de la enfermedad (157). Sin embargo, estas variantes se han asociado con la enfermedad de Crohn ( 157), colitis ulcerosa (159) y el cáncer colorrectal, aunque en este último caso hay informaciones contradictorias respecto al alelo que aumenta la susceptibilidad (160). En un reciente meta-análisis en el que se incluyen las variantes estudiadas en este trabajo se obseva una asociación con el incremento del riesgo de padecer cáncer gastrointestinal.…”
Section: Análisis De Polimorfismos En Genes Relacionados Con La Autofunclassified